2020
DOI: 10.1108/jpbafm-07-2020-0115
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering public budgeting after the COVID-19 outbreak: key lessons and future challenges

Abstract: PurposeThe paper aims to offer a viewpoint on how governmental budgeting needs to be reconsidered after the COVID-19 outbreak.Design/methodology/approachBuilding on extant research, and drawing on the Italian context, the paper provides reflections on four interrelated aspects: (1) how budgeting and reporting processes and formats are being modified; (2) how budgeting may enhance governments' financial resilience; (3) how citizens are involved in the budgeting cycles and (4) how emergency responses may produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 16 publications
1
60
0
4
Order By: Relevance
“…It presents the working assumptions behind the preparation of FY 2021 budgets and the budget balancing strategies employed when revenue shortfalls were anticipated. This research complements recent studies that have begun to explore local government issues around resilience in response to the pandemic, opportunities for innovation, and their accompanying challenges (Maher, Hoang, and Hindrey 2020;Dzigbede, Gehl, and Willoughby 2020;Anessi-Pessina et al 2020). Overall, the data suggest that local governments in North Carolina prepared for a recession by appropriating fund balance and using common cutback-management strategies that have been identified in the literature, like reductions in staffing including hiring freezes and budgeting for no new positions.…”
Section: Introductionsupporting
confidence: 63%
“…It presents the working assumptions behind the preparation of FY 2021 budgets and the budget balancing strategies employed when revenue shortfalls were anticipated. This research complements recent studies that have begun to explore local government issues around resilience in response to the pandemic, opportunities for innovation, and their accompanying challenges (Maher, Hoang, and Hindrey 2020;Dzigbede, Gehl, and Willoughby 2020;Anessi-Pessina et al 2020). Overall, the data suggest that local governments in North Carolina prepared for a recession by appropriating fund balance and using common cutback-management strategies that have been identified in the literature, like reductions in staffing including hiring freezes and budgeting for no new positions.…”
Section: Introductionsupporting
confidence: 63%
“…This could have long term fiscal consequences, potentially limiting the ability of governments to intervene in the future (Andrew et al, 2020). Likewise, in the Italian context, concerns have been raised that the increase and the emergency of these spendings might spur corruption (Anessi-Pessina et al, 2020). Future research should assess retrospectively, whether the observed shift in power is temporary or durable and which factors (e.g.…”
Section: Relation Of Covid-19mentioning
confidence: 99%
“…Observers have highlighted that policy tools used to counteract the impacts of the Covid-19 crisis have had a lot of similarities across countries, even though the sheer financial magnitude of such responses has varied extensively across jurisdictions (de Jong and Ho, 2020). Some municipalities have received funding to support specific Covid19 expenditures, others have been allowed to run deficits, while many central governments have intervened directly to support businesses and families (Anessi-Pessina et al, 2020).…”
Section: Assessing Financial Vulnerability In Crisesmentioning
confidence: 99%